Synthesis of monooxime-monocarbamoyl bispyridinium compounds bearing (E)-but-2-ene linker and evaluation of their reactivation activity against tabun- and paraoxon-inhibited acetylcholinesterase - Musilek, Kamil; Holas, Ondrej; Kuca, Kamil; Jun, Daniel; Dohnal, Vlastimil; Opletalova, Veronika; Dolezal, Martin (Journal of enzyme inhibition and medicinal chemistry, 2008)
Six AChE monooxime-monocarbamoyl reactivators with an (E)-but-2-ene linker were synthesized using modification of currently known synthetic pathways. Their potency to reactivate AChE inhibited by the nerve agent tabun and insecticide paraoxon was tested in vitro. The reactivation efficacies of pralidoxime, HI-6, obidoxime, K048, K075 and the newly prepared reactivators were compared. According to the results obtained, one reactivator seems to be promising against tabun-inhibited AChE and two reactivators against paraoxon-inhibited AChE. The best results were obtained for bisquaternary substances with at least one oxime group in position four.
Keywords: acetylcholinesterasa; Pyridinium Compounds; oximy; Cholinesterase Inhibitors; Paraoxon; organofosfáty; Carbamates; pyridinové sloučeniny; lidé; Oximes; karbamáty; cholinesterasové inhibitory; paraoxon; Acetylcholinesterase; Organophosphates; Humans